Addressing the Unfettered Authority of Sport Governing Bodies through EU Competition Law: The Effect of International Skating Union and European Super League - Ilias Bantekas (7628027) (2025)
The unfettered authority of sport-governing bodies (SGBs) has given rise to human rights claims and led to the distortion of EU free movement of persons and competition law. Following International Skating Union and European Super League Company, SBGs cannot exercise their right to achieve legitimate sporting aims like integrity and sporting fairness at the expense of competition rules. Nor are they allowed to prevent their member associations from organising/operating competitive leagues/events or to inflict sanctions on them for attempting to do so. These judgments will revolutionise the transnational sport law landscape, reshaping SGBs’ institutional rules and member relationships. Other Information Published in: Cambridge Yearbook of European Legal Studies License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1017/cel.2024.5